Arginine methylation by PRMT2 promotes IFN-β production through TLR4/IRF3 signaling pathway. (November 2021) - Wang, Juping; Hua, Haoming; Wang, Fanlu; Yang, Shuling; Zhou, Qinghong; Wu, Xiangsheng; Feng, Ding; Peng, Hui
Graphical abstract: Highlights: LPS induces TLR4 methylation by PRMT2 on R731 and R812. Arginine methylations on different sites mediates the interaction between TLR4 and IRF3. Arginine methylation on R285 induced by LPS activates IRF3. Arginine methylation of TLR4 on R812 induced by PRMT2 enhances IFN-β production. Protein arginine methylation positively regulates IFN-β production via TLR4/IRF3 signaling pathway. Abstract: A balance between the positive and negative regulation of toll-like receptor (TLR) signaling pathways is required to avoid detrimental and inappropriate inflammatory responses. Although some protein post-translational modifications (PTMs) such as phosphorylation and ubiquitination have been demonstrated to potently modulate innate immune responses, the role of methylation, an important PTM, control of TLR4 signaling pathway remains unclear. In this study, we found that protein arginine methyltransferase 1, 2 and 3 (PRMT1, 2 and 3) were recruited to methylate TLR4-CD (cytoplasmic domain) after lipopolysaccharide (LPS) stimulation respectively, but the effect of PRMT2 on arginine methylation of TLR4-CD is the most significant among above three PRMTs, which prompted us to focus on PRMT2. Reduction of PRMT2 expression down-regulated arginine (R) methylation level of TLR4 with or without LPS treatment. Methionine 115 (M115) mediated PRMT2 catalyzed-arginine methylation of TLR4 on R731 and R812. Furthermore, PRMT1, 2 and 3 was recruited to methylate interferon regulatory factor 3 (IRF3) after LPS stimulation respectively, but the effect of PRMT2 on arginine methylation of IRF3 is the most significant among the above three PRMTs. Arginine methylation of TLR4 on R812 or arginine methylation of IRF3 on R285 mediated the interaction between TLR4 and IRF3 respectively. Arginine methylation of IRF3 on R285 induced by LPS led to its dimerization and promoted its translocation from the cytoplasm to the nucleus. In addition, the enhancement of arginine methylation of TLR4 induced by PRMT1 or 2 increased IRF3 transcription activity with or without LPS treatment, while PRMT2 with histidine 112 glutamine (H112Q) or methionine 115 isoleucine (M115I) mutation and TLR4 with arginine 812 lysine (R812K) mutation decreased it. Arginine methylation of TLR4 on R812 or PRMT2 enhanced interferon-β (IFN-β) production. Our study reveals a critical role for PRMT2 and protein arginine methylation in the enhancement of IFN-β production via TLR4/IRF3 signaling pathway and may provide a therapeutic strategy to control endotoxemia.